PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, DEWAN KOMISARIS, DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN : STUDI EMPIRIS PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2021-2022 - Bernadette Elfrida; Rita Andini (Jurnal Ilmiah Ekonomika & Sains, 2025)
The purpose of this study: 1) To determine and analyze the effect of company size on company value, 2) To determine and analyze the effect of profitability on company value, 3) To determine and analyze the effect of leverage on company value, 4) To determine and analyze the effect of the board of commissioners on company value, 5) To determine and analyze the effect of Corporate Social Responsibility (CSR) on company value. The population in this study is all data from Energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2022, totaling 59 companies. This research was conducted by sampling with a purposive sampling technique, obtaining a sample of 31 companies. The analysis technique used is panel data regression. The results of this study can be concluded that: partially the company size variable has a positive effect, while the profitability, leverage, board of commissioners, and Corporate Social Responsibility (CSR) variables do not affect company value.